Ruang Publik Di Jembatan Penyeberangan Kota Jakarta: Sebuah Kajian Budaya - Sulhizah Wulan Sari (LPPM Universitas Bina Sarana Informatika, 2015)
This paper analyses the viaduct in Urban Jakarta as part of the public space through a cultural studies view. This study is important because the viaduct is not merely functioned as a service but also contested space that conceives with various interests and meanings. This study reveals the value system of the civils who live in Urban Jakarta and transformatory impact for human’s life. Public Space created contested space and meanings as memories, experiences, identities, consumerism, capilalism, and legitimated power. Those are constructed by history, economy, politic, social, and culture which changed the image of the viaduct to be meaningfull. The method uses in this study is descriptive qualitative. The result is this service created new space for lower middle class and be site of a power struggle.